Independent Authorities in the Field of Media in Algerian and French Law, a Comparative Study - Zeham, Abdella (Journal of Legal Studies and Researches, 2021)
The independent authorities in the media field are one of the guarantees of media freedom, The Algerian legal system has defined this type of authority in Law No. 90-07 just like the French legislator This type of authority was known under the name of the Supreme Council of Audiovisual. Therefore, we wanted, through this research, to clarify the independence of this type of authority in Algerian law compared to French law, and then find out which of the two systems seeks to provide the greatest degree of media freedom.